Doing Diversity in Museums and Heritage A Berlin Ethnography - Macdonald, Sharon (Cultural Heritage Studies, 2022)
The museum and heritage sector has been shaken by debates over how to address colonialism, migration, Islamophobia, LGBTI+ and multiple other forms of difference. This major multi-researcher ethnography of museums and heritage in Berlin provides new insight into how ›diversity‹ is understood and put into action in museums and heritage. Exploring new initiatives and approaches, the book shows how these work - or do not - in practice. By doing so, it highlights ways forward - for research and action - for the future. The fieldwork locations on which this book is based include the Humboldt Forum, the Museum of Islamic Art, the Museum für Naturkunde, and the Memorial to the Murdered Jews of Europe, as well as Berlin streets and protests.